Comparison of intravenous infusions of iloprost and oral nifedipine in treatment of Raynaud's phenomenon in patients with systemic sclerosis: a double blind randomised study. Issue 6673 (4th March 1989) - Rademaker, M.; Cooke, E. D.; Almond, N. E.; Beacham, J. A.; Smith, R. E.; Mant, T. G.; Kirby, J. D.
Abstract : OBJECTIVE--To compare the long term effects of short term intravenous infusions of iloprost with those of oral nifedipine in patients with Raynaud's phenomenon associated with systemic sclerosis. DESIGN--Double blind, placebo controlled, randomised group comparison. SETTING--Dermatology outpatient clinic. PATIENTS--Twenty three patients with Raynaud's phenomenon associated with well documented systemic sclerosis (American Rheumatism Association criteria) and with typical abnormalities in fingernail folds on capillaroscopy. INTERVENTIONS--Twelve patients were randomised to receive intravenous infusions of iloprost starting at 0.5 ng/kg/min and increased by 0.5 ng/kg/min every 15 minutes to a maximum of 2.0 ng/kg/min for eight hours on three consecutive days with a further single infusion at week 8. Placebo capsules were given concurrently. Eleven patients were randomised to receive nifedipine, starting at 30 mg daily and increased to 60 mg daily after four weeks for another 12 weeks. Infusions of placebo were given in the same manner as the infusions of iloprost. One patient from each group withdrew because of social reasons and three patients receiving nifedipine withdrew because of side effects. END POINT--Reduction in number, duration, and severity of attacks of Raynaud's phenomenon, reduction in number of digital lesions, increase in digital blood flow. MEASUREMENTS AND MAIN RESULTS--Measurements were taken at 0, 4, 8, 12, and 16 weeks. Both regimens produced a reduction in the number, duration, and severity of attacks of Raynaud's phenomenon. The mean (SE) number of digital lesions was reduced with iloprost (from 3.5 (1.6) to 0.6 (0.3] and with nifedipine (from 4.3 (0.8) to 1.4 (0.5] after 16 weeks. Hand temperature and digital and microcirculatory blood flow were increased with iloprost but not with nifedipine. CONCLUSION--Both iloprost and nifedipine are beneficial in the treatment of Raynaud's phenomenon. With nifedipine, however, side effects are common. Short term infusions of iloprost provide longlasting relief of symptoms, and side effects occur only during the infusions and are dose dependent.